Methods of organ-preservation of uterine fibroids. Is there a cause for debate? - V V Korennaya; N M Podzolkova; K V Puchkov (IP Berlin A.V., 2015)
Over the past years, new conservative methods of treatment of uterine fibroids and minimally invasive techniques that allow more frequent organ preserving interventions to take place. Accumulated experience allows us to compare the reproductive outcomes, quality of life in the postoperative period and other long-term results. Based on these data a gynecologist can make an informative decision about the optimal algorithm of patients with different clinical manifestations of myomas. This review presents recent data on the use of uterine artery embolization, the use of intrauterine shaver and possible ways of optimizing the laparoscopic myomectomy in order to improve the safety and efficacy of treatment.